2020
DOI: 10.1016/j.vetmic.2020.108748
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Respiratory Syncytial Virus Decreased Pasteurella multocida Adherence by Downregulating the Expression of Intercellular Adhesion Molecule-1 on the Surface of Upper Respiratory Epithelial Cells

Abstract: The synergistic infection of bovine respiratory syncytial virus (BRSV) and Pasteurella multocida (PM) may predispose cattle to develop severe pneumonia. Previously, we reported that BRSV infection significantly decreased PM adherence to the upper respiratory epithelial cells. It may allow bacteria to invade into the lower respiratory tract and lead to severe pneumonia. To investigate whether BRSV infection regulates the cell surface adherence receptor on bovine trachea epithelial cells (bTECs), we performed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…By capturing microbes, ICAM-1 displayed by cells of the upper respiratory tract acts as a "gateway" that impedes bacterial invasion of the lower respiratory tract (Sudaryatma et al, 2020). BRSV infection causes malfunction of ICAM-1 in the bovine upper respiratory tract, allowing bacterial invasion of the lower respiratory tract (Sudaryatma et al, 2020). The results of the present study demonstrated that BRSV infection increased PAFR expression in epithelial cells derived from the lower respiratory tract.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…By capturing microbes, ICAM-1 displayed by cells of the upper respiratory tract acts as a "gateway" that impedes bacterial invasion of the lower respiratory tract (Sudaryatma et al, 2020). BRSV infection causes malfunction of ICAM-1 in the bovine upper respiratory tract, allowing bacterial invasion of the lower respiratory tract (Sudaryatma et al, 2020). The results of the present study demonstrated that BRSV infection increased PAFR expression in epithelial cells derived from the lower respiratory tract.…”
Section: Discussionmentioning
confidence: 48%
“…In recent work (Sudaryatma et al, 2020), we have obtained evidence suggesting that the upper respiratory tract is responsible for inhibiting PM invasion of the lower respiratory tract. This inhibition is accomplished by trapping PM via ICAM-1, an adherence molecule that is displayed on the cellular surface under normal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the number of adhering bacteria decreased and increased in BRSV-infected cells derived from the upper and lower respiratory tract, respectively. These changes in the number of adhering bacteria were caused by down- and upregulation, respectively, of two bacterial adhesion molecules ( Sudaryatma et al, 2020a , 2020b ). Reduced and enhanced bacterial adherence to BRSV-infected upper and lower BRECs would permit bacteria to pass from the upper to lower respiratory tract, inducing severe pneumonia.…”
Section: Introductionmentioning
confidence: 99%